Analisis Lapangan Minat Konsumen Kota Palembang terhadap Penggunaan QRIS sebagai Alat Pembayaran Altenatif di Palembang Square Mall (Studi Kasus: Pengunjung Ps Mall) - Muhammad Aji Bakri; Reza Sagita; Maya Panorama; Romi Fadila (Universitas Batanghari Jambi, 2022)
This study examines the problem of payment methods via QR codes at Palembang Square Mall. The purpose of this research is to find out how many visitors to Palembang Square mall (PS Mall) use the QRIS code as an alternative payment method and to find out the barriers to PS Mall visitors using the QRIS code in terms of availability, effectiveness and efficiency, and the promos offered when using the QRIS code. This research was conducted using a qualitative method with a phenomology strategy. The results of the study were used as evaluation material for outlet owners at PS Mall to increase the interest of PS Mall visitors as well as Palembang city consumers in using QRIS as an alternative payment method.